Identifying Teaching Writing Strategies Used by English Teachers at SMK N 3 Singaraja During Remote Teaching - Handayani, Ni Nengah Diah; Suputra , Putu Eka Dambayana; Juniarta, Putu Adi Krisna (The Art of Teaching English as a Foreign Language (TATEFL), 2020)
The current study was carried out to identify the teaching writing strategies in remote teaching setting. This study was a case study. The study was conducted at SMK N 3 Singaraja. The participants of the current study were X grade English teachers of the 2020-2021 academic year, which consist of four teachers (2 females and 2 males). In conducting the study, observation and interview guide were used. The data were analyzed with guidance of analyzing qualitative data by Miles, Huberman, & Saldana (2014). The findings showed that the teaching writing strategies implemented by English teachers were guided writing, mind mapping, scaffolding, and dictogloss. In this remote teaching setting, English teachers are encouraged to be more creative in designing instruction and carrying the teaching strategies for teaching writing. Further study is suggested to identify teaching strategies used by English teacher in remote teaching for different language skills.